DETEKSI EKTOPARASIT Argulus sp. PADA BUDIDAYA IKAN KARPER (Cyprinus carpio L) DI UPTD- BALAI PENGEMBANGAN BUDIDAYA IKAN AIR TAWAR AIKMEL KABUPATEN LOMBOK TIMUR - kunti tirtasari (Fakultas Kedokteran Hewan Universitas Wijaya Kusuma Surabaya, 2020)
Argulus sp. is a fish louse disease that attacks fish on the outside of the body (Ectoparasites) resulting in wounds and bite marks being a trigger factor for the onset of other diseases (secondary diseases) resulting in losses for fish farmers. This research aims to find out if it detected Argulus ectoparasites sp in carper fish cultivation (Cyprinus carpio,L) in UPTD-BPBIAT Aikmel. This study uses a descriptive study design with observational survey type. Fish sampling is carried out using random sampling in one shot using a net with a total of 10 samples. Ectoparasite examination is carried out by making a direct observation then carried out the examination of the head, fins, tail with Alcohol Swabs 70%, . The research results shows that 9 fish were positive infectedwith Argulus sp